2008
DOI: 10.1002/adfm.200701313
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Hole‐Transporting Behavior of Discotic Liquid‐Crystalline Physical Gels

Abstract: Discotic liquid‐crystalline (LC) physical gels have been prepared by combining the self‐assembled fibers of a low‐molecular‐weight gelator and semiconducting LC triphenylene derivatives. The hole mobilities of the discotic LC physical gels measured by a time‐of‐flight method become higher than those of LC triphenylenes alone. The introduction of the finely dispersed networks of the gelator in the hexagonal columnar phases may affect the molecular dynamics of the liquid crystals, resulting in the enhancement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 91 publications
0
58
0
Order By: Relevance
“…However, the charge carrier transport in these systems can be improved. It was reported that the mobility of discotic triphenylenes can be increased though the formation of physical gels using a low molecular-weight gelator [14] or by complementary mixtures [15] Figure 6. The intra-columnar charge mobilities in the hexagonal, columnar mesophase (D h ) of various discotic compounds:…”
Section: à4mentioning
confidence: 99%
“…However, the charge carrier transport in these systems can be improved. It was reported that the mobility of discotic triphenylenes can be increased though the formation of physical gels using a low molecular-weight gelator [14] or by complementary mixtures [15] Figure 6. The intra-columnar charge mobilities in the hexagonal, columnar mesophase (D h ) of various discotic compounds:…”
Section: à4mentioning
confidence: 99%
“…The issue of flexible chain length in defining material characteristics has been discussed multiple times for semiconducting and/or supramolecular materials. [22,[24][25][26] However, comparatively few works have addressed structureproperty relations of molecular ferroelectrics in a systematic manner. [8,19,27] One of the few studies focusing on proper organic ferroelectric materials is by Kishikawa et al, who probed ferroelectric columnar hexagonal liquid crystalline urea with C 4 H 9 to C 16 H 33 long alkyl chains.…”
mentioning
confidence: 99%
“…In recent years, the fibrous supramolecular polymer network combining with the electrically switchable liquid crystal (LC) system have been developed as soft functional materials -LC physical gels [7][8][9][10]. The LC physical gels have been widely applied in various electro-optical devices, such as switchable scattering devices [11][12][13][14], LC semiconductors with high mobility [15,16], and stabilization of the orientation of ferroelectric LCs [17], etc. In particular, fast-response switching in twisted nematic (TN) cells based on the aid of fibrous polymer network have attracted more and more interests for their potential for improving the quality of LC displays (LCDs) [18][19][20].…”
Section: Introductionmentioning
confidence: 99%